TRANSFER OF INNOVATIONS: INFRASTRUCTURE ELEMENTS ORGANIZATION AND MANAGEMENT - Elena A. Midler; Natalya M. Ovanesyan; Igor V. Boguslavskiy (Advanced Engineering Research, 2012)
The innovation transfer system in terms of the integration of its disjoint infrastructural elements is considered. The establishing technique of the innovative brokerage institute as the most effective innovat ion management tool is considered. The local specificity and organization of the innovation infrastructure in case of the R ostov region are analyzed.